NUTRITION OF A HEALTHY CHILD DURING THE FIRST YEAR OF LIFE: IS IT ALL EVIDENT AND DO WE KNOW IT ALL? - I. N. ZAKHAROVA; I. N. KHOLODOVA; A. I. BRAGIN; V. V. NECHAEVA (Медицинский совет, 2017)
The authors raise the question of the role of goat milk in the nutrition of infants. The properties of goat milk and its difference from cow milk are discussed. The authors share experience in the prescription of goat milk formula, give examples from their own practice